Peningkatan Hasil Belajar PPKn dengan Metode Pembelajaran Role Reversal QuestionPada Siswa Kelas IX SMP Nahdlatut Tolibin Blega - Akhmad Sanusi; Jatim Desiyanto; Linda Ramadhanty Januar (Jurnal Cendekia Pendidikan, 2025)
This research is motivated by the low student learning outcomes in Civics subjects which include cognitive, affective, and psychomotor aspects. Low student participation in the learning process is one of the main causes, which is influenced by teaching methods that are less varied and are still one-way such as lectures. Lack of interaction, courage to ask questions, and lack of active student involvement make learning less effective and boring. This type of research is Classroom Action Research (PTK) which conducted in two cycles and involved 14 students of class IX SMP Nahdlatut Tholibin Blega as research subjects. Data collection techniques were conducted through tests, observations, questionnaires, and interviews. The learning method applied was Role Reversal Question, which is a learning strategy that involves exchanging roles between students as teachers and other students as participants in question and answer sessions, thus fostering a more lively and meaningful two-way interaction. The results showed that there was an increase in students' learning outcomes from pre-cycle to cycle II. In the pre-cycle stage, the average student score was 60.8 with a classical completeness of 24.3%. After applying the Role Reversal Question method in cycle I, the average score increased to 76.5 with 53.3% completeness. A more significant increase occurred in cycle II with an average score of 87.9 and completeness of 87.9%.